Liquid metal nanoparticles for the treatment of pancreatic cancer. - Xavierselvan, Marvin. (Tufts University. Tisch Library., 2023)
Pancreatic cancer is a highly aggressive and often fatal disease. One of the key challenges in treating pancreatic cancer is the presence of desmoplasia, a dense fibrous tissue that surrounds and supports the cancer cells. Desmoplasia contributes to tumor progression and resistance to therapy, and also limits the delivery of chemotherapy drugs to the cancer cells. The other challenge is the presence of hypoxia and acidosis in the tumor microenvironment which leads to drug efflux and immune cells suppression. Therefore, overcoming these difficulties is critical for improving the outcomes of pancreatic cancer treatment. Photodynamic therapy (PDT) is a non-invasive treatment modality that uses photosensitizer, light, and oxygen to selectively kill cancer cells. Preclinical studies have shown that PDT can reduce desmoplasia in pancreatic cancer, and early clinical trials have demonstrated promising results. However, to effectively combat pancreatic cancer, the photosensitizer needs to be delivered optimally. Herein, we present a drug delivery strategy for photosensitizers based on a new liquid metal nanoplatform that leverages the tumor microenvironment to achieve photodynamic therapeutic effects. Eutectic gallium indium (EGaIn) nanoparticles were successfully conjugated with a water-soluble cancer targeting ligand, hyaluronic acid, and a photosensitizer, benzoporphyrin derivative, creating EGaIn nanoparticles (EGaPs) via a simple green sonication method. The resulting EGaPs were stable over a month and had good biocompatibility with low cytotoxicity. Finally, photodynamic efficacy of EGaPs was investigated both in vitro and in vivo conditions to serve as multi-purpose nanoparticles for targeting, drug delivery, and photodynamic therapy.; 3-minute talk presented at the Tufts Graduate Student Council's 28th Graduate Student Research Symposium, April 19, 2023. 2nd place winner.